2022
DOI: 10.1371/journal.pgen.1010417
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions mediate discrete regulatory steps during fly spermatogenesis

Abstract: Gametogenesis requires coordinated signaling between germ cells and somatic cells. We previously showed that Gap junction (GJ)-mediated soma-germline communication is essential for fly spermatogenesis. Specifically, the GJ protein Innexin4/Zero population growth (Zpg) is necessary for somatic and germline stem cell maintenance and differentiation. It remains unknown how GJ-mediated signals regulate spermatogenesis or whether the function of these signals is restricted to the earliest stages of spermatogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have suggested a role of gap junction components in regulating soma-germline communication ( Starich et al, 2014 ). When gap junction between the soma and germline is disrupted, germline differentiation is blocked, and germline stem cells are not maintained ( Smendziuk et al, 2015 ; Huynh et al, 2022 ). Gap junctions are composed of innexin proteins in invertebrates ( Stebbings et al, 2002 ; Bauer et al, 2005 ; Beyer and Berthoud, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a role of gap junction components in regulating soma-germline communication ( Starich et al, 2014 ). When gap junction between the soma and germline is disrupted, germline differentiation is blocked, and germline stem cells are not maintained ( Smendziuk et al, 2015 ; Huynh et al, 2022 ). Gap junctions are composed of innexin proteins in invertebrates ( Stebbings et al, 2002 ; Bauer et al, 2005 ; Beyer and Berthoud, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Inx4 and Inx2 form gap junctions in the testis where they are required at different steps of sperm development (27,32,33).…”
Section: Introductionmentioning
confidence: 99%
“…such as the stretching of anterior follicle cells and the migration of border cells during stage 9 (6,29). Moreover, Inx4 and Inx2 form gap junctions in the testis where they are required at different steps of sperm development (27,32,33).…”
Section: Introductionmentioning
confidence: 99%